An investigation into the possible regulation of the expression of genes by yapA in Talaromyces marneffei using the qRT- PCR method. (8th December 2017) - Dankai, Wiyada; Pongpom, Monsicha; Vanittanakom, Nongnuch
Abstract: The pathogenic dimorphic fungus Talaromyces marneffei is known to cause a fatal systemic mycosis in immunocompromised patients, especially in HIV patients in Southeast Asia. The basic leucine-zipper (bZip) transcription factor gene, yapA, has been identified in T. marneffei . A prior study described that yapA was involved in the oxidative and nitrosative stress response in T. marneffei . Interestingly, an essential role of Saccharomyces cerevisiae Yap1p in the oxidative stress response is the activation of the transcription of its target genes. To identify the target genes of yapA in T. marneffei, the qRT-PCR method were used in this study. Investigation into the expression of genes which are probably regulated by yapA revealed that yapA controlled the expression of cat1 (catalase), cpeA (catalase-peroxidase), sodA (copper, zinc superoxide dismutase), gcs1 (glutamate-cysteine ligase), glr1 (glutathione oxidoreductase), trr1/trr2 (thioredoxin reductase), and trxA (thioredoxin) during stress conditions in all forms of conidium, mycelium, and yeast phase. An exception to this was the expression of cat1 under conditions of oxidative stress in the mould phase with a similar relative expression level in all of the wild-type, mutant and complemented strains. These genes are involved in response against oxidative stress and nitrosative stress in this fungus. The data showed that they could be regulated by the yapA gene during stress conditions. Moreover, the yapA gene is also known to control red pigment production by inhibiting the regulation of the five polyketide synthase ( pks ) genes, pks3 (polyketide synthase), rp1 (transcription activator), rp2 (β-subunit fatty acid synthase), rp3 (α-subunit fatty acid synthase), and rp4 (oxidoreductase) in the mould phase. In addition, it also regulates transcription in the laccase gene cluster including lac (extracellular dihydrogeodin oxidase/laccase), and multicopper oxidase encoding genes (PMAA_050860, PMAA_072680, PMAA_085520, PMAA_082010, and PMAA_082060) in all stages of the T. marneffei lifecycle (conidia, mould, and yeast phase). This study suggests the importance of the role of the yapA gene in the stress response and virulence of T. marneffei.